Association of renalase gene polymorphisms with the risk of hypertensive disorders of pregnancy in northeastern Han Chinese population. (1st November 2020) - Zhang, Feng; Liu, Wei; Wu, Yingnan; Li, Xiaoying; Zhang, Shuang; Feng, Yanan; Lu, Rui; Sun, Litao
Abstract: Renalase is a novel enzyme that can regulate blood pressure by degrading circulating catecholamines. We aimed to evaluate the possible effect of rs2296545, rs2576178 and rs10887800 polymorphisms of the renalase gene ( RNLS ) on the development of hypertensive disorders of pregnancy (HDP). This case-control study consisted of 185 patients with HDP and 380 normotensive pregnant women from the northeastern Chinese Han population. Association analyses were performed using PLINK, to compare allele and genotype frequencies in cases and controls. Adjustment for logistic regression analysis was performed by permutation testing. In the HDP patients compared with controls, we found that there was statistically significant difference in genotype distribution of rs2296545 ( p  = .037). Rs2296545 and rs2576178 polymorphisms have 1.91-fold ( p  = .004) and 1.73-fold ( p  = .015) increased risk of HDP in the dominant model, respectively. When compared preeclampsia (PE) to control, the RNLS rs2296545 polymorphism was significantly associated with PE risk in the dominant model ( p  = .021). We next analyzed the haplotypes of these SNPs and there was no difference between controls and HDP or PE. These findings suggest that rs2296545 was significantly associated with HDP and PE risk and the rs2576178 polymorphism may increase the susceptibility to HDP.